Risk of Cardiac Death After Adjuvant Radiotherapy for Breast Cancer - Giordano, Sharon H. (2005)
BACKGROUND: Women with breast cancer who are treated with adjuvant radiation have a decreased risk of local recurrence but an increased risk of mortality from ischemic heart disease. Patients with left-sided breast tumors receive a higher dose of radiation to the heart than patients with right-sided tumors. Because radiation techniques have improved over time, we investigated whether the risk of death from ischemic heart disease after adjuvant breast radiotherapy decreased over time. METHODS: We used the 12-registry 1973–2000 data-set from the National Cancer Institute’s Surveillance, Epidemiology, and End Results (SEER) program. Women (n = 27 283) treated with adjuvant radiation for breast cancer diagnosed in 1973–1989 were included in the study. Ischemic heart disease mortality was calculated at 15 years and compared for women diagnosed during 1973–1979, 1980–1984, and 1985–1989. Cox proportional hazards models were used to calculate the hazard of death from ischemic heart disease for women diagnosed 1973–1988 and censored at 12 years. All statistical tests were two-sided. RESULTS: There were no differences in age, race/ethnicity, disease stage, or follow-up time between the 13 998 women with left-sided and 13 285 with right-sided cancer. For women diagnosed in 1973–1979, there was a statistically significant difference in 15-year mortality from ischemic heart disease between patients with left-sided (13.1%, 95% confidence interval [CI] = 11.6 to 14.6) and those with right-sided (10.2%, 95% CI = 8.9 to 11.5) breast cancer (P = .02); no such difference was found for women diagnosed in 1980–1984 (9.4%, [95% CI = 8.1 to 10.6] versus 8.7% [95% CI = 7.4 to 10.0], respectively, P = .64) or 1985–1989 (5.8% [95% CI = 4.8 to 6.8] versus 5.2% [95% CI = 4.4 to 5.9], respectively, P = .98). In the Cox model, the hazard ratio [HR] for ischemic heart disease mortality for women with left-sided versus women with right-sided disease was 1.50 (95% CI = 1.19 to 1.87) in 1979. With each succeeding year after 1979, the hazard of death from ischemic heart disease for women with left-sided versus those with right-sided disease declined by 6% (HR = 0.94, 95% CI = 0.91 to 0.98). CONCLUSIONS: Risk of death from ischemic heart disease associated with radiation for breast cancer has substantially decreased over time.